A comparison of ICD-11 and DSM-5 criteria for PTSD among a representative sample of Chinese earthquake survivors. Issue 1 (31st December 2020) - Cao, Chengqi; Wang, Li; Wu, Jianhui; Bi, Yajie; Yang, Haibo; Fang, Ruojiao; Li, Gen; Liu, Ping; Luo, Shu; Hall, Brian J.; Elhai, Jon D.
ABSTRACT: Background: Striking differences regarding the diagnosis of PTSD exist between the ICD-11 and DSM-5. This study compared the prevalence and comorbidity of PTSD between the ICD-11 and DSM-5. Methods: An epidemiological sample of 1160 Chinese adult earthquake survivors collected nine and a half years following the Wenchuan earthquake, in Sichuan province. The PTSD Checklist for DSM-5 (PCL-5), the Patient Health Questionnaire (PHQ-9), and the Generalized Anxiety Disorder-7 (GAD-7) were used to measure PTSD, depression, and anxiety symptoms. Results: The ICD-11 PTSD criteria yielded higher prevalence estimates than the DSM-5 criteria. There were no significant differences in PTSD's comorbidity with major depressive disorder (MDD) or generalized anxiety disorder (GAD) between the ICD-11 and DSM-5 criteria. Conclusions: Results found that the ICD-11 and DSM-5 performed differently in assessing PTSD prevalence, but showed similar co-occurrence with MDD and GAD. This study adds to knowledge about the similarities and differences of using different PTSD criteria and carries implications for clinical and research utilization of the two widely used PTSD diagnostic criteria.